Development of E-Comics on Biotechnology Materials Equipped with Factual Videos for Scientific Literacy Skills - Lubis, Wahyuni (UIN Sunan Gunung Djati Bandung, 2025)
Biotechnology can be confusing. Comics make learning more engaging, fun, and understandable by telling stories. Innovation creates e-comics using factual recordings. This study examines the feasibility, readability, and student reactions to biotechnology e-comic media with factual videos. This study follows the ADDIE development methodology from analysis to design, development, implementation, and assessment. This study involved randomly selected grade XII students of Sultan Daulat 1 High School. This study found that 1) biotechnology e-comic media accompanied by factual videos had a material validation score of 84% and media validation of 93% with a very valid category. 2) Comic media obtained a readability score of 81.4% with a very good category. 3) Students' answers to comedy media obtained a very good score of 82%. These findings indicate that biotechnology e-comic media with factual videos is valid and can be used for learning.